KEKERASAN DALAM PENDIDIKAN - Siregar, Lis Yulianti Syafrida (Logaritma : Jurnal Ilmu-ilmu Pendidikan dan Sains, 2013)
AbstractBullying interprated as power or strength used for to hurt or intimidate others. This defenition give simple condition that hardness basically represent. Somtehing that done designedtly and loss to others made by loss is bullying action a such from physical an non-physical. Generally the problem of bullying is influenced by health of students soul and the import ant education of moralKeywords: bullying, helath of soul, education of moral